EFFECT OF BREED ON FUNCTIONAL CHARACTERISTICS OF FROZEN BULL SPERMATOZOA - NAGENDRAKUMAR, S B; KATHIRESAN, D (The Indian Journal of Animal Reproduction, 2011)
Semen samples collected from Jersey cross (n=6) and Friesian cross bulls (n=6) were extended in Tris-egg yolk-citric acid diluent. The samples were split and cryopreserved in static vapor freezing and programmed freezing. A significant influence of breed was evident on the progressive motility, percentage of intact acrosome and loss of enzyme Aspartate transaminase while a non significant influence was noticed on the hypo-osmotic swelling response and percentage of live spermatozoa with intact acrosome. It was evident from the present investigation that the there is selective influence of breed on the functional characteristics of frozen thawed semen processed by routine freezing protocols and by programmed freezing.